(untitled) - Kegan, Robert (Boston, Mass, 2009)
This persuasive and practical book, filled with hands-on diagnostics and compelling case studies, delivers the tools you need to overcome the forces of inertia and transform your life and your work.
Keywords: Đổi mới công nghệ,Industrial management,Technological innovations,Quản lý công nghiệp; Quản lý,Management; Hoa Kỳ,United States,United States,Hoa Kỳ